(untitled) (KYAMC Journal, 2026)
Background: Poor R wave progression on electrocardiography has long been associated with anterior myocardial infarction. However, in contemporary practice, its structural and functional correlates are inconsistent, and the true echocardiographic implications remain incompletely characterized. Objectives: To determine the prevalence of echocardiographic abnormalities among patients with poor R-wave progression and to assess their associations with socio-demographic factors, cardiovascular risk factors, comorbidities, and clinical symptoms. Materials and Methods: This hospital-based cross-sectional study included 196 adults with poor R-wave progression on standard 12-lead electrocardiography. All participants underwent transthoracic echocardiography to evaluate regional wall motion abnormalities, left ventricular hypertrophy, prior myocardial infarction patterns, and left ventricular ejection fraction. Categorical variables were summarized as frequencies and percentages. Associations between clinical variables and echocardiographic findings were assessed using Pearson’s chi-square test. Multivariable binary logistic regression was performed to identify independent predictors of regional wall motion abnormalities. A two-sided p-value <0.05 was considered statistically significant. Results: Regional wall motion abnormalities were present in 67.9% of participants, and 50.5% demonstrated reduced left ventricular ejection fraction (<50%). Overall, 77.0% exhibited at least one echocardiographic abnormality. Hypertension was significantly associated with reduced ejection fraction (p=0.002). Shortness of breath on exertion showed a strong association with reduced ejection fraction (p<0.001), and male gender was also significantly associated with reduced ejection fraction (p=0.022). No significant association was observed between age group and regional wall motion abnormalities. Conclusion: Poor R-wave progression is frequently associated with clinically relevant structural and functional myocardial abnormalities. Echocardiographic evaluation should be considered to identify underlying ventricular dysfunction in affected patients. KYAMC Journal Vol. 16, No. 03, October 2025: 123-130.